The Meaning of Transformational Leadership for High School Teachers: Perspectives on Work Climate and Performance in Banda Aceh - Nurrizayani, Nurrizayani; Niswanto, Niswanto; Usman, Nasir; Ismail, Ismail (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to examine the meaning of transformational leadership for high school teachers in Banda Aceh, with a focus on the work climate and performance. Using a descriptive qualitative approach, data were obtained through in-depth interviews, observations, and documentation with 15 teachers from five high schools. The results of the study show that transformational leadership increases motivation, creativity, and collaboration among teachers, as well as creates a positive work climate. In addition, this leadership also has a significant effect on improving teacher performance. Despite challenges such as resistance to change and limited resources, this study suggests the importance of adapting leadership styles to local contexts to create better quality education.